2009
DOI: 10.1097/pas.0b013e318196d018
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Features of Ulcerative Colitis in Patients With Primary Sclerosing Cholangitis

Abstract: UC patients with PSC show a propensity for more extensive, but less active, disease but are otherwise characterized by similar pathologic findings compared with UC patients without PSC. Rectal sparing and patchy disease activity is not characteristic of UC patients with PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(105 citation statements)
references
References 34 publications
5
95
1
1
Order By: Relevance
“…On the other hand, some authors reported tendency for pancolitis in PSC-UC, and no statistically significant difference in the frequency of rectal sparing and backwash ileitis, using stricter histologic definitions. 134 In keeping with recent findings, 134 one population-based cohort study reported that backwash ileitis and rectal sparing were rare in PSC-UC. 132 These discrepancies may be due to study population, geographical location, disease presentation, and definition of pancolitis, backwash ileitis, and rectal sparing.…”
Section: Clinicopathologic Characteristicssupporting
confidence: 75%
“…On the other hand, some authors reported tendency for pancolitis in PSC-UC, and no statistically significant difference in the frequency of rectal sparing and backwash ileitis, using stricter histologic definitions. 134 In keeping with recent findings, 134 one population-based cohort study reported that backwash ileitis and rectal sparing were rare in PSC-UC. 132 These discrepancies may be due to study population, geographical location, disease presentation, and definition of pancolitis, backwash ileitis, and rectal sparing.…”
Section: Clinicopathologic Characteristicssupporting
confidence: 75%
“…A recent case -control study found no difference between patients with PSC plus IBD and IBD alone in terms of rectal sparing. The same investigators found similar backwash ileitis prevalences in the PSC plus UC group and the UC alone group (Joo et al, 2009). It was suggested that patients with PSC and UC may more likely run a quiescent course of colitis than UC patients without coexistent PSC.…”
Section: Impact Of Coexisting Psc On the Disease Behavior And Course mentioning
confidence: 67%
“…While UC can be diagnosed many years after PSC diagnosis and even after orthotopic liver transplantation(OLT), a patient with UC, who had a proctocolectomy or not, can be diagnosed with PSC many years later (Joo et al,2009). …”
Section: Impact Of Coexisting Psc On the Disease Behavior And Course mentioning
confidence: 99%
See 1 more Smart Citation
“…They could remain without symptoms for many years and have a median survival transplantation free of 12 years. 86 Although asymptomatic, some patients may have advanced disease, as evaluated both histologically and radiologically. Symptomatic patients may present with fever, jaundice, pruritus, and right upper quadrant pain.…”
Section: Clinical Featuresmentioning
confidence: 99%